Successful correction of inverted nipple using silicone implants: A pioneering surgical approach - Bruce P. Dos-Santos; Mireia Ruiz-Castilla (JPRAS Open, 2024)
Inverted nipples are commonly observed and can lead to challenges in breastfeeding, sexual experiences, and dissatisfaction with one's physical appearance. Currently, there is a lack of consensus on the optimal treatment approach. The use of a smooth silicone implant to reconstruct the nipple-areola complex in post-mastectomy breast reconstruction has recently been proposed. This study presents the first case using this approach in a patient with a grade II inverted nipple who previously failed conventional reconstructive surgical treatment.